HUMAN RESOURCE AND ARCHIVE MANAGEMENT APPLICATION FOR THE REGIONAL CIVIL SERVICE POLICE AND FIRE DEPARTMENT IN TAPIN - Akbar, Ferdy Yudillah; Hasanuddin, Hasanuddin; Yuridka, Fitrah (Transpublika Publisher, 2023)
The use of personnel applications for data collection and archiving employee information is crucial for every agency, including the Civil Service Police Unit and Tapin Fire Department. Despite having existing means for personnel data collection and archiving, the agency lacks a proficient personnel application. Currently, data collection and archiving are still carried out manually using Microsoft Word and Excel. Additionally, some data is stored in hard copy form and placed in binders, making it susceptible to damage or loss. Recognizing these challenges, the idea of developing a website-based personnel application emerged to streamline the personnel department's processes. The chosen programming languages for this application are PHP, HTML, and the Laravel Framework, with MySQL as the database. The research employed the waterfall model, incorporating data collection techniques such as observation, interviews, and documentation. The research findings reveal that the Tapin Civil Service Police Unit and Tapin Fire Department lack a competent human resources application. Consequently, a comprehensive application has been developed to address these shortcomings. Test results demonstrate that the application's features function as intended. In essence, the creation of this application has successfully met its primary objective of addressing data collection and archiving issues within the Civil Service Police Unit and Tapin Fire Department.